Alternativas sócioambientais para gestão comunitária no assentamento do Tarumã Mirim, Manaus - AM - (:unkn) unknown (Universidade Federal do Amazonas, 2006)
The land registration in the Tarumã Mirim micro basin is very relevant ecologically to Manaus city; it is inserted between two hydrographic basins: Tarumã Mirim and Tarumã Açu. Thereby, the research, whose theme SOCIO ENVOIROMENTAL ALTERNATIVES TO COMMUNITY MANAGEMENT IN TARUMÃ MIRIM LAND REGISTRATION MANAUS-AM has its merit due to the elaboration of an environmental socio-economical management of the place. The method used was Rapid Participative Diagnosis (RPD), which had as goal the raising of social, economics and environmental data from the region. Besides, the research questionnaires were applied to the land registration residents to complement information found in the RPD and compare individual opinions with group work to the quantitative survey of socio-economical and environmental characteristics of the land registration communities. This was extracted by a group of adults of both genders in aleatory way derived from 173 families. We conclude that the results found were that the government has promoted a deficient agricultural politics with an inefficient agricultural politics remarkable by its incompetence in promoting quality of life to rural population (health improvement, drainage and residence; education with special attention to agricultural learning, food, literacy, production and also development of partnership and others) having the weakness of man fixation in countryside as a consequence of it. It is time to question the functionality and transparence of the truth gave by the government and to establish goals not only to projects creation but also to the feasibility of them.
Keywords: Assentamento rural; Gestão da Conservação Ambiental; Sócioambiental e política agrícola; Participação comunitária; Reforma agrária; Socioenvironmental and agricultural politic; CIÊNCIAS AGRÁRIAS